Identification of risk factors and high-risk areas for transmission of intestinal parasites in model locality in Slovakia - Lukáš Ihnacik; Júlia Šmigová; Ingrid Papajová (Scientific Reports)
Abstract Intestinal parasitoses remain a significant health concern, particularly in populations living in areas with poor hygiene and poor living conditions. These infections can cause intestinal problems and pose health risks, especially for children. In Slovakia, such infections are concentrated around Roma settlements. The most effective protection against intestinal parasitoses requires raising public awareness about the disease in general, which is usually lacking. A parasitological analysis using sedimentation methods revealed that 5.95% of the 2,503 stool samples collected from 59 villages in the Rožňava region tested positive for intestinal parasites. The most prevalent species were Ascaris lumbricoides and Giardia duodenalis. Results of the chi-squared test of independence showed a significantly higher infection rate among people from Roma communities and also among residents from rural areas. Correlation analysis identified population density, access to water and sanitation, and education levels as key factors influencing infection rates. Spatial analysis further highlighted areas at higher risk of contracting intestinal parasite diseases within the study area. Ultimately, the insights and information gained from this study can contribute to the development of better-targeted strategies for reducing the occurrence of intestinal parasitoses and improving the overall health situation for the inhabitants of these marginalised areas.